Adolf Cluss’ mark on the earliest Grade School in Spain (Foro de Educacion, 2014)
The school of Cartagena, inaugurated in 1904, was the first school built in Spain to host a graded school –consisted of a set of classrooms organized under the principles of graded education, from the lower to the higher levels-. The origin of the graded school from Cartagena is commonly accepted to be in the capital city of the United States of America. This research suggests that the design of the school of Cartagena was inspired by the Wallach School, named after the mayor Richard Wallach and designed by Adolf Cluss, German American architect, which was inaugurated in Washington D.C. in 1864 and demolished in 1950.